Multidisciplinary team-based nursing of a patient with uremia and severe stasis dermatitis (多学科团队协作模式下1例尿毒症合并重度淤积性皮炎患者的护理体会) - WANG Lu (王露); YANG Ting (杨婷); YIN Xiaoning (尹小宁); ZHAO Xia (赵霞) (中西医结合护理)
This paper reported the multidisciplinary team approach in nursing of a patient with uremia and severe stasis dermatitis. A comprehensive nursing plan based on the multidisciplinary team was established after assessment of illness condition of the patient. Key issues of nursing included correcting heart failure, controlling hyperkalemia, dialysis and detoxification, nutritional support, and preventing catheter-related bloodstream infections, catheterization guided by digital subtraction angiography, multidisciplinary team collaboration, local and systemic drug therapy, and Traditional Chinese Medicine nursing technology. The comprehensive nursing strategy effectively relieved the clinical symptom, reduced the risk of complication and improved the patient’s quality of life during treatment. (本文总结多学科团队(MDT)协作模式下1例尿毒症合并重度淤积性皮炎患者的护理体会。患者病情复杂, 基于MDT模式, 采取综合护理策略, 包括纠正心衰、控制高钾血症、透析排毒、营养支持及预防导管相关血流感染、数字减影血管造影引导下血管通路置管、多学科诊疗协作、局部及系统药物治疗, 以及中医护理方法, 降低了并发症风险, 有效改善了患者的症状和生活质量。)